Sol-gel organic-inorganic composites for 3-D holographic lithography of photonic crystals with submicron periodicity - Saravanamuttu, K; Blanford, C; Sharp, D; Dedman, E; Turberfield, A; Denning, R (2003)
We demonstrate that silica-acrylate materials doped with transition metal (Zr, Ti) oxide nanoparticles are suitable for the three-dimensional holographic lithography of photonic crystals with submicron periodicity and large inorganic contents. By careful choice of inorganic components, such composites could provide a route to the template-free, direct lithography of three-dimensionally ordered structures with high refractive-index contrast, submicron periodicity, and band gaps in the visible and infrared regions.